Potential role of APOE ɛ4 allele as a modifier for the association of BDNF Val66Met polymorphisms and cognitive impairment in community-dwelling older adults - Ji, Shaozhen; Kang, Jia; Han, Chao; Xu, Xitong; Chen, Meijie; Chen, Jie; Chhetri, Jagadish K; Pan, Jing; Chan, Piu (Frontiers in Aging Neuroscience, 2024)
Objective To determine whether the brain-derived neurotrophic factor (BDNF) Val66Met polymorphism is associated with cognitive impairment (CI) in community-dwelling Chinese older adults, and to investigate whether this relationship is modified by the Apolipoprotein E (APOE) ɛ4 allele. Methods The study is a secondary analysis of 703 participants aged ≥60 years randomly enrolled from the Beijing Longitudinal Study of Aging II prospective cohort. The education-adjusted Mini-Mental State Examination and the Clinical Dementia Rating Scale were used to measure the cognitive performance of the subjects. The main effects and interactions (additive and multiplicative) of the BDNF Met and the APOE ε4 alleles on CI were estimated by logistic regression models. Results In total, 84 out of 703 older adults aged ≥60 years old had CI. No significant difference was observed in the risk of CI between participants with the BDNF Met allele and that of subjects without the BDNF Met allele (p = 0.213; p = 0.164). Individuals carrying both the BDNF Met and APOE ε4 alleles had an almost 1.5-fold increased odds of CI compared with carriers of the BDNF Met allele but without the APOE ε4 allele. The additive association indicated a positive interaction of both BDNF Met and APOE ε4 alleles with wide CIs (p = 0.021; p = 0.018). Conclusion The results suggest that the APOE ε4 allele may be a potential modifier for the association of the BDNF Val66Met polymorphism with CI in community-dwelling older adults.